A self-assembled carrier-free nanosonosensitizer for photoacoustic imaging-guided synergistic chemo–sonodynamic cancer therapy. Issue 9 (26th February 2020) - Dong, Caihong; Jiang, Qvzi; Qian, Xiaoqin; Wu, Wencheng; Wang, Wenping; Yu, Luodan; Chen, Yu
Abstract : Nanosonosensitizer, Ce6-PTX@IR783, successfully realized the photoacoustic imaging-guided synergistic chemo–sonodynamic therapy with ultrasound-trigged controllable drug release and acquired high therapeutic efficacy for cancer. Abstract : As one of the most promising noninvasive therapeutic modalities, sonodynamic therapy (SDT) can focus the ultrasound energy on tumor sites located in deep tissue and locally activate the preloaded sonosensitizer to kill tumor cells. However, exploring sonosensitizers with high SDT efficacy and desirable biosafety is still a significant challenge. Herein, we utilized the hydrophilic–hydrophobic self-assembly technology to assemble the hydrophobic organic dye Ce6 and broad spectral anti-cancer agent Paclitaxel with hydrophilic organic dye IR783 to generate a nanoscale sonosensitizer, Ce6-PTX@IR783, without the introduction of extra nanomaterials into the fabrication to guarantee high therapeutic biosafety and further potential clinical translation. The constructed nanodrug was endowed with an external ultrasound-activatable chemo–sonodynamic effect and photoacoustic imaging performance via integrating multiple moieties into one nanosystem. Ce6 could enhance the sonodynamic effect, while PTX exerted a chemotherapeutic effect, and IR783 was applied to increase tumor-specific accumulation and assist in fulfilling photoacoustic imaging. In particular, the small particle size (70 nm) of Ce6-PTX@IR783 contributed to the increased tumor accumulation via the enhanced permeability and retention effect. The high synergistically chemo–sonodynamic therapeutic efficacy has been successfully demonstrated in vitro and in vivo, in addition to the demonstrated high biodegradability, biocompatibility and biosafety. This facile self-assembly procedure provides an intriguing strategy for highly efficient utilization of hydrophobic drugs and is liable to realize large-scale production and further clinical translation.